Answer:
The final velocity,
, is gd.
Step-by-step explanation:
The condition here is a free falling object. Thus from the third equation of motion under free fall, we have;
=
+ 2gs
where
is the final velocity of the object,
is the initial velocity of the object, g is the gravitational force and s is the height.
Since the object falls from a height of d, then
= 0 m/s, and s = d.
So that;
= 0 + 2gd
= 2gd
= 2gd
When the distance is
,
= 0 m/s.
Then;
= 2g
![(d)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ylu6ff6jppgchbuk6zhhrtj1tdam1upkam.png)
= g x d
When the object falls through the height
, then the final velocity is gd.